The Effect of Freeze/ Thaw Conditions on Hydrogel Lens Posterior Apical Radius and Surface Quality - Janoff, Lester E (Canadian Journal of Optometry, 1982)
Twenty-six hydrogel lenses of identical parameters were subjected to twenty-five freeze/ thaw cycles and periodically checked for base curve sagittal depth and surface quality. A matched group of lenses served as an untreated control. The results indicated the treatment group gave more stable measurements than the control group. No surface defects were apparent after twenty-five cycles. It may well be that the freeze/thaw cycle relieves the internal stress created by machining a complex polymer. We are confident that hydrogel lenses of simple HEMA formulations when subject to freeze/ thaw conditions, are unharmed.